Oncologic outcomes and prognostic impact of urothelial recurrences in patients undergoing segmental and total ureterectomy for upper tract urothelial carcinoma - Pereira Pedrosa, Jose Alexandre; Masterson, Timothy A.; Rice, Kevin R.; Kaimakliotis, Hristos Z.; Monn, M. Francesca; Bihrle, Richard; Koch, Michael O.; Boris, Ronald S. (Canadian Urological Association Journal, 2015)
Introduction: We evaluated the impact of urothelial recurrences in a cohort of patients undergoing segmental (SU) and total ureterectomy (TU) as an alternative to nephroureterectomy (NU) for upper tract urothelial carcinoma. Methods: Between 1999 and 2012, patients who underwent SU, TU and NU for treatment of upper tract urothelial carcinoma were evaluated. Demographic, surgical, pathologic and oncologic data were collected. Recurrence-free (RFS) and disease-specific survival (DSS) were analyzed using Kaplan-Meier and multivariable Cox methods. Results: A total 141 patients were evaluated, 35 underwent SU, 10 TU and 96 NU. Patients who underwent TU were more likely to have bilateral disease (p < 0.01), solitary kidney (p < 0.01), and multifocal disease (p = 0.01). Organ-confined (p < 0.01) and lowgrade disease (p < 0.01) were more common in the TU and SU groups compared with NU. At a median follow-up of 56.9 months (range: 0.2–181.1) disease relapse occurred in 88 (55.3%) patients. Localized recurrence occurred in 31.1% of SU/TU group compared to 27.1% (p = 0.62) of the NU group. Neither total nor segmental ureterectomy demonstrated significantly worse RFS (p = 0.26 and p = 0.81), CSS (p = 0.96 and p = 0.52) or overall survival (p = 0.59 and p = 0.55) compared with complete NU. Localized urothelial recurrence did not confer increased risk of cancer-specific (p = 0.73) or overall mortality (p = 0.39). The paper’s most important limitations include its retrospective nature and its relatively small number of patients. Conclusion: No significant survival differences were demonstrated between surgical approaches for upper tract urothelial cancer. Localized urothelial recurrence after surgical treatment for upper tract urothelial cancer does not affect mortality in this population. TU with ileal-substitution may provide an alternative option for patients with extensive ureteral disease and poor renal function.